Corrigendum: Novel Cesium Resistance Mechanism of Alkaliphilic Bacterium Isolated From Jumping Spider Ground Extract - Koretsune, Takahiro; Ishida, Yoshiki; Kaneda, Yuri; Ishiuchi, Eri; Teshima, Miyu; Marubashi, Nanami; Satoh, Katsuya; Ito, Masahiro (Frontiers in Microbiology, 2022)
The radionuclide isotopes (134Cs　and 137Cs) of Cesium (Cs), an alkali metal, are attracting attention as major causes of radioactive contamination. Although Cs+ is harmful to the growth of plants and bacteria, alkaliphilic bacterium Microbacterium sp. TS-1, isolated from a jumping spider, showed growth even in the presence of 1.2 M CsCl. The maximum concentration of Cs+ that microorganisms can withstand has been reported to be 700 mM till date, suggesting that the strain TS-1 is resistant to a high-concentration of Cs ions. Multiple reports of cesium ion-resistant bacteria have been reported, but the detailed mechanism has not yet been elucidated. We obtained Cs ion-sensitive mutants and their revertant mutants from strain TS-1 and identified a Cs ion-resistance-related gene, MTS1_00475, by performing SNP analysis of the whole-genome sequence data. When exposed to more than 200 mM Cs+ concentration, the intracellular Cs+ concentration was constantly lowered by MTS1_00475, which encodes the novel low-affinity Cs+/H+ antiporter. This study is the first to clarify the mechanism of cesium resistance in unexplained cesium-resistant microorganisms. By clarifying the new cesium resistance mechanism, it can be expected to be used as a bioremediation tool for treating radioactive Cs+ contaminated water.